Location of three canals in the mesiobuccal root of the maxillary first molar - Andressa Salles Gonçalves Pais (RSBO Revista Sul-Brasileira de Odontologia, 2012)
Introduction: The knowledge on the complex anatomy of the maxillary first molar and location of extra canals are essential for diagnosis and endodontic treatment success. Objective: The purpose of this study was to report a clinical case showing a varied number of root canals in maxillary molars with the aid of the operating microscope (OM). Case report: The endodontic retreatment of the right maxillary first molar with unusual anatomical variation was performed, displaying three canals in the mesiobuccal root (MB), a root canal in the distobuccal root (DV) and a root canal in the palatal root (P). To remove the resin core inside pulp chamber with and without the aid of dental operating microscope, a high-speed drill and ultrasonic tip (diamond round) was used, respectively, for the refinement of the pulp chamber walls. The dental operating microscope was used during the access surgery, location, negotiation of canals and checking of the completion of all stages of the retreatment. Subsequently, the cleaning, shaping and filling of the root canal system was completed. The presence of three canals in the mesiobuccal root, one in the distobuccal root and one in the palatal root was found. Conclusion: Variations in the number of canals could be confirmed during the surgery access in endodontic retreatment cases with the aid of dental operating microscope.